2022
DOI: 10.1002/jcp.30823
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine effect of the stromal vascular fraction containing M2 macrophages on human chondrocytes through the Smad2/3 signaling pathway

Abstract: The adipose-derived stromal vascular fraction (SVF) is composed of a heterogeneous mix of adipose-derived stem cells (ADSCs), macrophages, pericytes, fibroblasts, blood, and other cells. Previous studies have found that the paracrine effects of SVF cells may be therapeutic, but their role in osteoarthritis treatment remains unclear.This study aimed to investigate the therapeutic effect of SVF cells on chondrocytes.Chondrocytes were seeded on culture plates alone (control) or cocultured with SVF or ADSCs on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…M2Φ secrete TGF-β and IL-10, induce collagen II expression in chondrocytes, and decrease MMP-13 expression [50]. Previous studies have reported that co-culture of the SVF or ADSCs with isolated pellets produces notably larger pellets in the SVF group than in the ADSC group [30,32]. Our results support these ndings: moreover, the M2Φ group showed a larger pellet size than the ADSC group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…M2Φ secrete TGF-β and IL-10, induce collagen II expression in chondrocytes, and decrease MMP-13 expression [50]. Previous studies have reported that co-culture of the SVF or ADSCs with isolated pellets produces notably larger pellets in the SVF group than in the ADSC group [30,32]. Our results support these ndings: moreover, the M2Φ group showed a larger pellet size than the ADSC group.…”
Section: Discussionsupporting
confidence: 88%
“…The rats were divided into three groups and received injections of the SVF containing 1 × 10 5 cells (SVF group), 1 × 10 4 ADSCs (ADSC group), or 100 µL of PBS (control group). Based on previous reports [32], in this study, the SVF/ADSC ratio was set at 10%, and the SVF and ADSC groups included equivalent amounts of ADSCs to determine the therapeutic potential of the heterogeneous cells in SVF.…”
Section: Preparation Of the Svf And Adscsmentioning
confidence: 99%
“…Another study showed that SVF was superior to platelet-rich plasma for reducing pain associated with knee OA from 1 month to 1 year postoperatively [ 29 ]. This may be because SVF cells promote inhibitory macrophages and T-regulatory cells, which have stronger pain-relieving effects because of reduced inflammatory markers [ 30 , 31 ]. Experiments involving animal models have confirmed the anti-inflammatory effects of SVF on knee OA [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages secrete TGF-β and IL-10, induce collagen II expression in chondrocytes, and decrease MMP-13 expression [53]. Additionally, TGF-β has been recently reported to contribute to chondrocyte regeneration partially through the Smad2/3 signaling pathway [54]. Macrophages that have acquired the M2 phenotype upregulate the expression of anti-in ammatory cytokines, including IL-10 and TGF-β, when co-cultured with MSCs and ADSCs [55].…”
Section: Discussionmentioning
confidence: 99%